(untitled) (Journal of the College of Basic Education, 2022)
The current study presents a study of the external appearance of the species Balclutha rubrostriata Melichar 1903, where the study showed a detailed description and illustrations of the characteristics of the external appearance and patterns of spots in the forehead, face, and dorsal front and middle breasts or the front and back wings, the shape of the male abdominal base, the seventh abdominal sternum of the female, and the system of spines distribution For the genital plate and genital stylus of the male genitals, also the shape of the penis, the ligament, the middle and lower valves, the oviposition apparatus, the veining systems on the fore and hind wings.